Gdy recenzent traci głowę. Odpowiedź Katarzynie Pejdzie - Rogacz, Dawid (Humaniora. Czasopismo Internetowe, 2026)
The paper responds to the review of the Polish edition of Rogacz’s “Chinese Philosophy of History” made by Katarzyna Pejda. The response extensively demonstrates that the review is not only simplistic and superficial but also directly at odds with the book’s central claims and its use of the source material.